Choroidal thickness profile in healthy Indian children - Chhablani, Jay; Deshpande, Riddhima; Sachdeva, Virender; Vidya, Sagar; Rao, P; Panigati, Anand; Mahat, Birendra; Pappuru, Rajeev; Pehere, Niranjan; Pathengay, Avinash (Indian journal of ophthalmology, 2015)
Purpose: The purpose was to study choroidal thickness and its profile based on location in healthy Indian children using enhanced depth spectral-domain-optical coherence tomography (SD-OCT). Methods: In this cross-sectional observational study 255 eyes of 136 children with no retinal or choroidal disease were consecutively scanned using enhanced depth SD-OCT. Eyes with any ocular disease or axial length (AXL) >25 mm or < 20 mm were excluded. A single observer measured choroidal thickness from the posterior edge of the retinal pigment epithelium to the choroid/sclera junction at 500-microns intervals up to 2500 microns temporal and nasal to the fovea. Generalized estimating equations were used to evaluate the correlation between choroidal thickness at various locations and age, AXL, gender and spherical equivalent (SEq). Results: Mean age of the subjects was 11.9 ± 3.4 years (range: 5-18 years). There were 62 Females and 74 males. The mean AXL was 23.55 ± 0.74 mm. Mean subfoveal choroidal thickness was 312.1 ± 45.40 μm. Choroid was found to be thickest subfoveally, then temporally. Age, AXL and SEq showed a significant correlation with choroidal thickness, whereas gender did not affect choroidal thickness. Conclusion: Our study provides a valid normative database of choroidal thickness in healthy Indian children. This database could be useful for further studies evaluating choroidal changes in various chorioretinal disorders. Age and AXL are critical factors, which negatively correlated with choroidal thickness.